ECONOMICS MODERNIZATION TASKS AND RUSSIAN FEDERATION ECONOMIC DEVELOPMENT PLANNING SYSTEM - O. O. Smirnova (Модернизация, инновация, развитие, 2016)
A system of strategic planning documents at the federal and regional levels of the Russian Federation is proposed. A standard on compulsory structure of strategic planning documents for both the country and its regions should be fixed by law. The standard should also include a systemof predictive planning, indicative planning, monitoring, strategy development and other activities to be followed by governmental bodies for the planned indicators to be reached.